Optimalisasi Peran Humas Pemerintah Kabupaten Nagan Raya Era Digitalisasi sebagai Upaya Mewujudkan Transparansi Informasi Publik - Shanda Anggraini; Desi Maulida (Penerbit Goodwood, 2023)
Purpose: This study aims to determine the optimization of the role of public relations for the Nagan Raya district government in digitalization era as effort to realize public information transparency. Method: Research is a type of descriptive qualitative research whit data collection techniques in the form of literature reviews and interviews. The object of study is optimizing the role of public relations Nagan Raya district government in the digitalization era as an effort to realize transparency of public information with the public relations subject of the Nagan Raya district government. Research data was taken trough direct interviews whit representatives of public relations. Results: The results of the study show that public relations has an important role as a mediator in disseminating information to make it easier for the public to access the information provided. In the era digitalization, public relations make adaptations that utilize new media in conveying information in order to realize transparency of public information. However, there are also challenges experienced by public relations, namely the limited human resources that are competent in the field of digital and information technology, which causes the publication content to not be optimal. For the reason, effort are needed such as recruiting competent human resources and providing training for staff so they can adopt digitalization. Limitations: This research only collects data through interviews so that the data findings are still limited. Contribution: This research can contribute to government public relations in maximizing its role in the digital era, specifically in improving for the optimal strategy for the role of public relations in conveying information.